Effectiveness of audiovisual media to improve mental health knowledge for adolescents: A systematic review - Samsul Arif P; Shanti Wardaningsih (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
The tagline "no health without mental health" is real evidence of mental health's vital role in mental health problems. Mental health problem conditions could be prevented with a low-cost tendency by improving mental health awareness specifically improving and decreasing the stigma. This effort is useful to ensure the mental health treatment process is effective for everyone, including adolescents. The research collected and analyzed the audio-visual intervention model and the effectiveness of the model to improve the mental health knowledge of adolescence. This research applied a systematic review with the approach of PICO criteria. The researchers also used PRISMA as the review guideline.  The applied databases were ProQuest, ScienceDirect, Springer, Taylor Francis, Sage, and Google Scholar. The researchers found 747 articles. Then, the researchers analyzed the articles with PICO and PRISMA. The researchers found 9 articles based on the inclusion and exclusion criteria. Then, the researchers analyzed the articles. The analysis results showed that all models or audiovisual media intervention forms could improve the mental health knowledge of adolescence. The models of the audiovisual interventions were: Tele Mental Health/ Teletherapy/ Digital Mental Health; Boca Norte (audiovisual narrative/ digital teen series); Bibliodrama/experience of death education; Video; the face-to-face teen; Online Discussion Team; and What’s Up With Everyone/ WUWE.  Conclusion the intervention results found the effectiveness of improving mental health knowledge for adolescents. Abstrak: Tagline “No Health without mental health” merupakan bukti nyata bahwa kesehatan mental memainkan peran sangat vital pada permasalahan kesehatan manusia. Kondisi kesehatan mental umumnya dapat dilakukan pencegahan yang cenderung membutuhkan biaya murah yakni meningkatkan kesadaran kesehatan mental khususnya meningkatkan pemahaman dan mengurangi stigma sehingga proses treatment kesehatan mental menjadi efektif pada setiap tingkatan termasuk remaja.  Tujuan penelitian untuk mengumpulkan dan menganalisa model intervensi audiovisual dan keefektifan dalam meningkatkan pengetahuan kesehatan mental pada remaja. Penelitian ini menggunakan sistematis review dengan pendekatan kriteria PICO dan sebagai panduan melakukan review menggunakan PRISMA.  Database yang digunakan antara lain ProQuest, ScienceDirect, Springer, Taylor Francis, Sage dan google scholar ditemukan sebanyak 747 artikel yang kemudian setelah diterapkan analisa menggunakan PICO dan PRISMA didapatkan 9 artikel yang sesuai kriteria inklusi dan eksklusi yang kemudian dilakukan analisis. Hasil penelitian ini analisa menunjukkan semua model/ bentuk intervensi media audiovisual meningkatkan pengetahuan kesehatan mental pada remaja dan model/ bentuk intervensi audiovisual diantaranya Tele Mental Health/ Teletherapy/ Digital Mental Health; Boca Norte (audiovisual narative/ digital teen series); Bibliodrama/ experince of death education; Video; the face-to-face teen; Kelompok Diskusi Online; dan What’s Up With Everyone/ WUWE. kesimpulan hasil intervensi tersebut terbukti efektif dalam meningkatkan pengetahuan kesehatan mental pada remaja.